1999
DOI: 10.1086/313242
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of Hα Accretion Regions in Algol Binaries

Abstract: We have investigated a group of 18 Algol-type binaries to determine the general morphologies and physical properties of the accretion regions in these systems. The systems studied were V505 Sgr, RZ Cas, AI Dra, TV Cas, TW Cas, d Lib, RW Tau, TW Dra, b Per, TX UMa, U Sge, S Equ, U CrB, RS Vul, SW Cyg, CX Dra, TT Hya, and AU Mon, in order of increasing orbital period P \ 1.18È11.11 days. In addition, the RS CVn-type binary HR 1099 (V711 Tau) was observed to illustrate the appearance of chromospheric Ha emission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 81 publications
5
109
1
Order By: Relevance
“…Richards & Albright 1999). Evidence for inter-system matter, emitting and absorbing at Hα wavelengths, has been also recently reported by Marino et al (2001) for HR 7428, a long-period, detached atypical RS CVn binary composed of a bright K-type giant and an A-type star.…”
Section: Analysis Of the Hα Linesupporting
confidence: 60%
“…Richards & Albright 1999). Evidence for inter-system matter, emitting and absorbing at Hα wavelengths, has been also recently reported by Marino et al (2001) for HR 7428, a long-period, detached atypical RS CVn binary composed of a bright K-type giant and an A-type star.…”
Section: Analysis Of the Hα Linesupporting
confidence: 60%
“…Manzoori & Gozaliazl (2007) have determined a value forṖ (thusṀ) and have seen a hot spot on the gainer's surface for which a range of temperatures is given by Richards & Albright (1999). A value for L add has been determined by Albright & Richards (1996), which makes this binary a well-described system.…”
Section: Discussionmentioning
confidence: 99%
“…-SW Cyg: masses, radii, and effective temperatures can be found in the catalog of Budding (2004) and Richards & Albright (1999). Values forṖ (and thusṀ) are from Qian et al (2002).…”
Section: A2 Three Gainers With An Accretion Diskmentioning
confidence: 99%
“…The secular period increase rates were obtained as DP=P ¼ 0:102 s yr À1 and DP=P ¼ 0:03 s yr À1 for S Equ and AB Cas, respectively, requiring mass transfer rates of about dM=dt ¼ 3:97 Â 10 À8 M yr À1 and dM=dt ¼ 5:6 Â 10 À8 M yr À1 from Roche lobe-filling low-mass secondaries to the primaries. Richards & Albright (1999) reported that S Equ shows emission lines in its spectra due to an accretion disk structure resulting from mass transfer. In addition, Vesper et al (2001) showed, using spectral data, that the system has an accretion structure.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The spectral types of the hotter and cooler components are B7 V and G8 III, respectively (Plavec 1983). Its spectra show single-peaked emission features with additional weak double-peaked emission at some epochs, indicating mass transfer activity and disk structure around the primary component (see, e.g., Richards & Albright 1999;Vesper, Honeycutt, & Hunt 2001). Although OÀC curves were published by several authors (Plavec 1966;Kreiner 1971), there was has been no detailed period study of the system.…”
Section: Introductionmentioning
confidence: 99%